Examining the roles of rule following, reinforcement, and preexprerimental histories on risk-taking behavior. - Dixon, Mark R.; Hayes, Linda J.; Aban, Immaculada B. (Psychological Record)
The purpose of the present study was to examine the participation of a variety of variables in gambling behavior. Forty-five subjects were exposed to an experimental roulette game played for course extra-credit points. In Phase 1, subjects played a fair game (i.e., completely random outcomes) without any instructions regarding the programmed contingencies for 75 trials. During Phase 2, subjects were exposed to an adjusted game with payback percentages of either p = .2, p = .8, or continued at p = fair and instructions related to play. Lastly, during Phase 3 all subjects were exposed to an adjusted game with a payback percentage of .2 and an option for escape. Results show that subjects exposed to inaccurate rules regarding play took higher levels of risk, made larger bets, and chose the escape option later than subjects exposed to accurate or no rules related to play. Although reinforcement density varied across subjects exposed to the same rule condition, there was no significant effect of that manipulation on subsequent gambles. Reprinted by permission of the publisher.